Simultaneous sleep study and nasoendoscopic investigation in a patient with obstructive sleep apnoea syndrome refractory to continuous positive airway pressure: a case report - Loureiro, CC (2009)
INTRODUCTION: The standard treatment for obstructive sleep apnoea syndrome is nasal continuous positive airway pressure. In most cases the obstruction is located at the oropharyngeal level, and nasal continuous positive airway pressure is usually effective. In cases of non-response to nasal continuous positive airway pressure other treatments like mandibular advancement devices or upper airway surgery (especially bi-maxillary advancement) may also be considered. CASE PRESENTATION: We report the case of a 38-year-old Caucasian man with severe obstructive sleep apnoea syndrome, initially refractory to nasal continuous positive airway pressure (and subsequently also to a mandibular advancement devices), in which the visualization of the upper airway with sleep endoscopy and the concomitant titration of positive pressure were useful in the investigation and resolution of sleep disordered breathing. In fact, there was a marked reduction in the size of his nasopharynx, and a paresis of his left aryepiglotic fold with hypertrophy of the right aryepiglotic fold. The application of bi-level positive airway pressure and an oral interface successfully managed his obstructive sleep apnoea. CONCLUSION: This is a rare case of obstructive sleep apnoea syndrome refractory to treatment with nocturnal ventilatory support. Visualization of the endoscopic changes, during sleep and under positive pressure, was of great value to understanding the mechanisms of refractoriness. It also oriented the therapeutic option. Refractoriness to obstructive sleep apnoea therapy with continuous positive airway pressure is rare, and each case should be approached individually.